Chemical Composition of Essential Oil of Cendana Frangipani Flower (Plumeria alba) With Re-Extraction Using Ethanol Solvents - Ni Made Wartini; GP Ganda Putra; Putu Timur Ina (Agroindustrial Journal, 2017)
One potential source of essential oils in Bali which has not been developed is from cendana frangipani flower. Cendana frangipani flower has a very distinctive scent and very popular in Bali, it has an important function in the local culture, used as fragrances, incense (prayer facilities especially in Bali), and as an air freshener aromatherapy in the spa industry. The fragrance is typical due to their volatile oil which content in the cendana frangipani flower. The quality produced of essential oils are determined by their chemical composition of the extraction process. Previous research indicates that the good quality of frangipani immature essential oil extractedthrough the extraction process using hexane resulting in concrete form which still has the solvent aroma, semi-solid consistency and dark yellow. Therefore, it is necessary tomodifythe process by changing the concrete into the absolute product by re- extraction using ethanol.The purpose of this study was to determine the differences in chemical composition of essential oils of cendana frangipani flowers resulting from the re-extraction by using a particular comparison between ethanol and concrete. Fresh cendana frangipani flowers were sliced and then extracted with n-hexane in a Soxhlet extractor toproduce concrete volatile oil. The concrete was further re-extracted using absolute ethanol to produce essential oil with a concrete and ethanol comparison treatment consisting of 1:4, 1:6, 1:8, and 1:10. Absolute essential oil were then analyzed by GC-MS. The analysis showed that the absolute cendana frangipani flower essential oil produced by different treatment has a different compounds composition and relative percentages varied. The chemical composition of cendana frangipani absolute essential oils was classified as alcohols, terpenes, ketones, esters, and acid with the concentration from 2.65 to 24.77%;0.34 to 1.35%; 0 to 1.38 %; 13.38 to 24.23% and from 22.74 to 58.15% respectively.